Towards low-cost sodium-ion batteries: electrode behavior of graphite electrodes obtained from spheroidization waste fractions and their structure-property relations. (1st January 2023) - Escher, Ines; Mancini, Marilena; Martin, Jan; Janßen, Knut Arne; Axmann, Peter; Adelhelm, Philipp
Abstract: Electrode materials for lithium-ion batteries (LIBs) typically show spherical particle shapes. For cathode materials, the spherical shape is obtained through the synthesis method. For graphite, the by far most popular anode material for LIBs, spherical particles are obtained through a spheroidization process. The yield of that process is quite low and limited to about 50%, leaving substantial amounts of by-products. Using such lower quality by-products would be quite attractive for developing low-cost energy stores like sodium-ion batteries (SIBs), for which the requirements for particle sizes and shapes might be less strict as compared to high performing LIBs. Here, we study three different graphite 'waste fractions' as anode material for SIBs that are obtained from the spheroidization process and how they compare to LIB battery grade material. Only negligible differences between the fractions are found when analyzing them with x-ray diffraction (XRD), Raman spectroscopy and elemental analysis (EA). More clear differences can be seen from N2 physisorption, scanning electron microscopy (SEM) and particle size analysis. For example, the surface areas of the 'waste fractions' can become roughly up to twice as large as compared to the battery grade fraction and the d 50 values shift by up to 11.9 µ m to lower numbers. Electrochemical measurements show that the 'waste fractions' can deliver the full electrode capacity and behave similar to the battery grade fraction up to 10 C. However, the higher surface areas lead to more irreversible losses in the first cycle. A surprising finding is that all graphite fractions show almost identical discharge voltages, while the charging voltages differ by as much as 200 mV. This asymmetric behavior only occurs in SIBs and not in LIBs, which indicates a more complex storage behavior in case of sodium.